2020
DOI: 10.1097/md.0000000000022278
|View full text |Cite
|
Sign up to set email alerts
|

Association of MMP-9 polymorphisms with diabetic nephropathy risk

Abstract: Background: Diabetic nephropathy (DN) is a multifactorial disease with gene–environment interaction resulting in progressive renal function damage. Multiple studies have assessed the association between matrix metalloproteinase-9 (MMP-9) gene promoter polymorphism and DN susceptibility. However, the results are inconclusive. In the present study, we will conduct a meta-analysis to further examine this relationship more precisely. Methods: Electronic databases (Pubmed, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The pathophysiological background of this association is the fact that this variant of MMP-9 decreases binding potential of the proteins involved in the inhibition of transcription to the DNA sequence, thus playing a role in orchestrating the transcription activity of MMP-9 [81]. Rather interestingly, this polymorphism exerts a protective role in a wide spectrum of diseases, such as diabetic nephropathy and anterior open bite [82,83]. In a large prospective trial (n = 1127) that included patients with CAD, the association between MMP-9 levels and the risk of fatal CV events showed a hazard ratio of 1.3, even after adjustment for confounders in terms of therapy and other clinical confounders whereas multivariate regression analysis by Ezhov et al disclosed that MMP-9 is a strong independent predictor of plaque instability in stable CAD patients [84].…”
Section: Inflammation-based Biomarkersmentioning
confidence: 99%
“…The pathophysiological background of this association is the fact that this variant of MMP-9 decreases binding potential of the proteins involved in the inhibition of transcription to the DNA sequence, thus playing a role in orchestrating the transcription activity of MMP-9 [81]. Rather interestingly, this polymorphism exerts a protective role in a wide spectrum of diseases, such as diabetic nephropathy and anterior open bite [82,83]. In a large prospective trial (n = 1127) that included patients with CAD, the association between MMP-9 levels and the risk of fatal CV events showed a hazard ratio of 1.3, even after adjustment for confounders in terms of therapy and other clinical confounders whereas multivariate regression analysis by Ezhov et al disclosed that MMP-9 is a strong independent predictor of plaque instability in stable CAD patients [84].…”
Section: Inflammation-based Biomarkersmentioning
confidence: 99%
“…MMP-9 might be crucial for leukocyte migration and regional extracellular matrix proteolysis. Furthermore, numerous investigations have demonstrated that MMP-9 acts as a crucial inflammatory indicator, thus influencing the pathophysiology of DN ( Xie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple genetic variants have been identified to be linked with the pathogenesis of DN and can serve as a potential biomarker for early prevention and detection of the disease 16–28 . Matrix metalloproteinases (MMPs) are a large family of zinc and calcium dependent endopeptidases expressed in both developing and adult kidneys 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…14 Multiple genetic variants have been identified to be linked with the pathogenesis of DN and can serve as a potential biomarker for early prevention and detection of the disease. [16][17][18][19][20][21][22][23][24][25][26][27][28] Matrix metalloproteinases (MMPs) are a large family of zinc and calcium dependent endopeptidases expressed in both developing and adult kidneys. 29,30 They are critical mediators of extracellular matrix (ECM) degradation and turnover in the kidney during normal matrix remodeling.…”
mentioning
confidence: 99%